Utilization of seaweed (Gracilaria sp.) liquid as cost- effective macronutrients and micronutrients for bioethanol production - Zakaria, Nur Z.I.; Gunny, Ahmad Anas Nagoor; Dzahir, Mohd I.H.M; Ahmad, Abdul Aziz; Ismail, Ku S.K; Mahmod, Safa Senan; Javed, Muhammad; Yazdi, Namdar B; Saifuddin, Md. N.A.A (AIDIC-Italian Association of Chemical Engineering, 2023)
Seaweed liquid waste from filter-squeezed drying process of Gracilaria sp. causes an unpleasant odour to the environment. Although this waste can partially be used as biofertilizer and heavy metals adsorbent, a bigger portion of the waste remains unutilized thus causing a problem to the environment. The present study aimed to utilize seaweed liquid waste as a supplement in fermentation media. To achieve this aim, Saccharomyces cerevisiae as a famous bioethanol producer was used to examine the ability of seaweed liquid to supply macronutrients and micronutrients in the media to produce ethanol. Interestingly, when used as a supplement in the fermentation media to produce ethanol, the liquid boosted ethanol production three folds from 200 mg/L of 2 % glucose alone to 600 mg/L of 2 % glucose in liquid. Additionally, the liquid was able to substitute yeast extract and peptone within YPD media to produce 647.48 mg/L ethanol as compared to only 542.39 mg/L with normal YPD which contains yeast extract and peptone. For that reason, the utilization of seaweed liquid as the supplement in the medium should be considered as an alternative cost-effective media for enhancing ethanol production without the addition of other nutrients.